The Quality of Life in Heart Failure Reduced Ejection Fraction (HFrEF) Patients: A Phenomenon of Obesity Paradox - Rachmawan, Yogi Puji; Pratiwi, Witri; Helda, Helda (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
Background: Obesity place patients at risk of cardiovascular disease (CVD). There may be an inverse relationship between obesity and CVD prognosis-a phenomenon known as the “obesity paradox”. Obese HF patients might have a better prognosis, especially in terms of quality of life (QoL). Aims: The purpose of this study was to examine the QoL of HF patients based on obesity classification. Methods: This cross-sectional study was conducted at the HF clinic of Hasna Medika Cardiovascular Hospital, Cirebon, Indonesia. Samples were HFrEF patients who had received medication at the HF clinic for at least 6 months and the patient must have received optimal guidelines directed medical therapy (GDMT) with at least 3 pillar drugs according to Indonesian heart failure guidelines. Inclusion criteria were HF patients with ejection fraction <40% on echocardiographic examination. Exclusion criteria were HF patients with motor impairments, such as post-stroke, severe osteoarthritis, paralysis, and patients who did not receive optimal GDMT. Results: A total of 40.3% sample were obese, 9.7% were underweight and 67.5% had central obesity. Coronary artery disease (89.6%), smoking (67.5%) and hypertension (49.4%) were the most common comorbidities and risk factors found. About 12.3% of sample experienced rehospitalization 3 times a year. Based on Kansas City Cardiomyopathy Questionnaire (KCCQ)-12, about 3.2% of the sample had poor QoL, 55.8% had good QoL and 9.7% had excellent QoL. HFrEF patients with excellent QoL had a proportion of 66.7% obese and 20% overweight. While there were no obese patients in HFrEF patients with poor QoL. The proportion of HFrEF patients with excellent QoL who had central obesity was 80%. Meanwhile, 65.1% of HFrEF patients with good QoL were obese. Conclusion: Obese HF patients have better QoL outcomes. This phenomenon is called obesity paradox. A good quality of life in HF patients is an important goal of HF management in addition to reducing mortality. Received: 02 December 2024 | Reviewed: 17 December 2024 | Revised: 24 December 2024 | Accepted: 10 January 2025.